An explanatory case report about critical differences of ‘inability to work’ in Italian welfare and social security systems - Michele Sammicheli; Marcella Scaglione (Journal of Health and Social Sciences)
In Italy, there is a different status of ‘inability to work’ in civil invalidity and INPS social security insurance systems. These differences and overlaps cause some concerns. We show a case report of a 55-year-old woman with a recent left radical mastectomy and ipsilateral lymphadenectomy, for infiltrating ductal and lobular carcinoma. The woman, showing no radiological evidence of metastases, was undergoing chemotherapy with taxanes and cisplatin. The patient reported no significant osteo-articular functional limitations, with the exception of a reduction in left shoulder movements at extreme degrees in a right-handed person, due to the recent mastectomy and complained nausea and vomiting due to chemotherapy. The civil invalidity committee assessed her as being disabled, with a total and permanent incapacity for work as 100%, whereas the INPS Medical Legal Department (C.M.L.) recognised her as disabled in employments suitable for her capabilities (article 1 of Law no 222/1984), but not incapable of carrying out any works (article 2 of Law no 222/1984). Progress in medicine and workplace adjustments may enable employees with disabilities to come back work. Therefore, knowledge of these differences and overlaps and the role of legal practitioners and policymakers could be decisive resulting in a source of savings for the Italian welfare system.